(3GdCfhGQ GdLdGdjI aj TQM GdaUhd GdfUjQjIs - (3GdSjhQj, GdMdj, GdCSOj, CHh YHO Gddg, TQa GdOjf, ebOGO Hf YHO Gddg Hf eMeO Hf GdMSjf, J (B826s
(3ChdgG (B:s
(3SHMGfc Gddge hGLO GdhLhO (B... (3adeG cGf Yde GdcdGe ef Hjf gPg GdYdhe ChKb HQgGfG hCXgQ hCTQa ehVYG hCced CUhdG haQhYG hdPdc GSJMb GdJbOje Ydi SGFQ GdYdhe hJfRd efgG efRdI GdTeS (B...s
(3BNQgG (B:s
.. (3Cbhd NJe GdeUfa QMeg Gddg QSGdJg HgPg GdfUjMI heVehfgG GdMK Ydi YHGOI Gddg JYGdi hGdbjGe HMbg HMSH GdLgO hGdWGbI hPdc dCfg EPG fXQ HYjf Ybdg Cj JacQg hHUjQJg aj NdbJg heG GhOY ajgG ef GdMce hGdEJbGf (B...(3hGdMeO ddgs
(3JHUQI GdeDda (B:s
(3Ydi XgQjI GdeNWhW Cf GdeDda gh (B( (3LdGd GdOjf GdLQLGfj (B) (3MajO GdeJQLe Yf GdfU GdaGQSj Qcf GdOjf eMeO Hf Ydj GdLQLGfj GdMdj GdZQhj , hdcf UGMH GdPQjYI jPcQ Cfg (B: " (3UOQg HGSe Gdedc LdGd GdOjf Ydj Hf TQa GdOjf GdeQJVi GdYdhj GdMSjfj GdBhj hSeGg HGSeg(B" .s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\282s
(3GdPQjYI (B2/1670s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds